2010
DOI: 10.1111/j.2042-3292.2010.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of traumatic tracheal collapse with extraluminal titanium mesh screens

Abstract: Summary A 12‐year‐old Thoroughbred gelding presented with a history of exercise intolerance and inspiratory stridor. Physical examination revealed a blunt crush injury to the ventral neck and underlying trachea of unknown duration. Tracheoscopy revealed a grade 3 tracheal collapse. Surgical management of the case involved placement of extraluminal titanium mesh screens circumferentially around the trachea for complete support. During the period of hospitalisation, the only post operative complication was serom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
0
14
0
5
Order By: Relevance
“…However, unstable tracheal rings should be repaired using suture or alternatively intraluminal titanium mesh screens (Scott ; Graham et al . ). If fractured tracheal rings are not stabilised, malalignment can result in a reduction in the diameter of the trachea, or the formation of a chondroma (Haynes ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, unstable tracheal rings should be repaired using suture or alternatively intraluminal titanium mesh screens (Scott ; Graham et al . ). If fractured tracheal rings are not stabilised, malalignment can result in a reduction in the diameter of the trachea, or the formation of a chondroma (Haynes ).…”
Section: Discussionmentioning
confidence: 97%
“…While this condition is usually caused by a kick or other trauma by running into a fence in horses (Trostle et al 1995;Saulez et al 2005Saulez et al , 2009, iatrogenic perforations of the trachea have also been reported following endotracheal intubation (Saulez et al 2009). Single perforations have been reported to occur dorsally (Gronvold et al 2005;Saulez et al 2005Saulez et al , 2009), ventrally (Graham et al 2010) or laterally (Caron and Townsend 1984). The horses described in this report had concurrent dorsal and ventral perforations, a rarely reported finding (Cudmore and Nath 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly true in cases of blunt trauma that damages the trachea or oesophagus. Injury to the tracheal rings can occur without perforation and may not be noticed initially, as was the case with the horse described in the article by Graham et al . (2010) in this issue.…”
mentioning
confidence: 89%